"Just Having a Job": Career Advancement for Low-Wage Workers With Intellectual and Developmental Disabilities. (May 2014) - Lindstrom, Lauren; Hirano, Kara A.; McCarthy, Colleen; Alverson, Charlotte Y.
This study examined career development and early employment experiences for four young adults with intellectual and developmental disabilities. Researchers used a multiple-method, multiple case-study longitudinal design to explore career development within the context of family systems, high school and transition programs, adult services, and early and continued experiences in the labor market. Data sources included school and rehabilitation records, job observations, and interviews with young adults, family members, high school special education personnel, employers, and adult agency staff ( N = 39). During the early career years, participants maintained stable employment, but earned annual wages well under the federal poverty line. Employment opportunities seemed to be influenced by family advocacy and expectations, school-based work experiences, job development services, and work environments.